Creation of Heterosis Hybrids of Cucumis Melo L. for the Protected Soil of Uzbekistan (Eurasian Research Bulletin, 2022)
For the first time in the republic, varieties of hothouse melons were created, which are distinguished by high yield, high palatability, resistance to major diseases common in protected ground. The hybrid F1 Zarkhal was submitted to the variety testing inspection, and the promising hybrids F1 L-160 × L-179 and F1 L-161 × L-179 are undergoing production tests in greenhouses of the republic